Influential factors and structural reliability - Eusuf, Muhammad Abu; Al Hasan, Abdullah (Trans Tech Publications Ltd., Switzerland, 2013)
This study focuses on the influential factors that enhance the reliability and versatility of structure throughout the life span. The factors are considered on the basis of the need for assessment of state of –art- structural analysis and design. Through investigation the researcher found that there are two most influential factors are repeatedly influencing the life of structure. The two factors are structural elements and loading patterns. Structural elements are identified on the basis of structure height, span, bays, percentage of shear wall, ratio of structural and non- structural panels to total number of panels and type of frame. The loading pattern investigated on the serviceability limit of structural components.